Cognitive-behaviour therapy case conceptualisation and psychotherapeutic practice : the practitioner's perspective : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Küsel, Kim Brigitte (Massey University, 2012)
Cognitive Behaviour Therapy (CBT) is the most-widely utilised therapeutic approach in New Zealand; with case conceptualisation identified as “the heart”, or “cornerstone”, of CBT practice. Yet, there is limited empirical support for CBT case conceptualisation; and an identified paucity of research regarding its real-world use. As such, the present study investigated the real-world, case conceptualisation practices, attitudes and experiences of 48 New Zealand CBT practitioners; with the primary aim of exploring CBT case conceptualisation within the context of the practitioners’ subjective perspective. The data set consisted of responses to a purpose-built survey, while data analysis took the form of a descriptive analysis, which in turn, informed a thematic based review of the themes within the data. The descriptive results revealed that almost all respondents are utilising CBT-specific, case-level conceptualisations in their practices; they appear to have a good understanding of the various components of case conceptualisation, and appear to mirror the recommended theory in both their theoretical understanding, and practical use of conceptualisation. Utilising the descriptive results as a context, a thematic analysis was used to identify the main and sub-themes embedded in the responses. “Conceptualisation as a Highly Valued Therapeutic Process” was identified as the single main theme. The first sub-theme, “The Indicators that respondents value case conceptualisation”; included the following additional sub-themes: The high level of conceptualisation use among respondents; the pursuit of further education about case conceptualisation; the use of conceptualisation-compatible therapeutic tools; and the qualities that respondents attributed to conceptualisation; and informed the overall theme of conceptualisation as a valued process. The second sub-theme, “The practitioner-perceived benefits of conceptualisation”, contained three sub-themes, each examining the benefits of CBT case conceptualisation to either the practitioner, the client, or, the therapeutic process; was informed by the main theme, and explores why respondents value conceptualisation. These findings; together with the limitations, implications and future directions, of this study are discussed in the context current literature and the research aims.
Keywords: Cognitive therapy; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Psychology::Applied psychology